Effects of undergraduate leadership experiences on leadership efficacy - Leone, Deanna Josephine Maria, author; Chermack, Thomas, advisor; Hughes, Blanche, committee member; McKelfresh, David, committee member; Rastall, Patrick, committee member (Colorado State University. Libraries, 2015)
This dissertation addressed the research problem burdening higher education to better prepare students with leadership they can effectively apply in complex organizational environments during a time of rising costs for education and competing interests for programmatic funding. This context coupled with high costs for corporate training to generate performance improvements and increased spending on leadership development during a recognized crisis in organizational leadership in the U.S. increased pressure on employers to hire college graduates who can enter the workforce with demonstrated leadership capacity. To address the research problem, the purpose of this non-experimental research study explored the relationships between leadership experiences on leadership efficacy by comparing strength of associations and differences in undergraduate students at Colorado State University through a secondary analysis of data collected during the Multi-Institutional Study of Leadership in 2006, 2009, and 2012. The research design and rationale included between-groups mixed factorial design using independent samples t-tests, factorial analysis, and regression analysis as the inferential statistics for data analysis and exploration of how the independent variable - leadership experiences - might predict the dependent variable - leadership efficacy. Target population for this study was undergraduate students enrolled at Colorado State University's main campus. As part of the Multi-Institutional Study of Leadership in 2006, 2009, and 2012, two sampled populations were drawn from the undergraduate population each year, which included 1) a random sampled population up to 4,000 participants, and 2) a purposefully sampled comparative population identified from rosters of campus leadership experiences. Results of statistical analysis indicated high internal consistency reliability for leadership efficacy data with a 0.88 Cronbach's coefficient alpha. Assumptions of independence, normality, and linearity were met. Principal component factor analysis supported construct validity of the data used to create the MSL leadership efficacy scales with 73% of the total variance explained by only one component. Results of independent t-tests indicated higher average leadership efficacy scores for students reporting yes to having leadership experience while in college (Mdifference = 0.27,p<.001), but the effect of the significance was small (d = 0.23). There was no statistical significance reported for the interaction between leadership experience and the year the MSL survey was administered on predicting leadership efficacy, F(2,3223) = 1.09, p = 0.34, partial eta² = 0.001. Results of the multiple regression analysis indicated that short-term and long-term leadership experiences had a statistically significant effect on predicting higher average scores for leadership efficacy at a 99% confidence interval. Leadership courses also had a positive effect also on predicting higher average leadership efficacy scores at a 95% confidence interval. The combination of experiences was also statistically significant (p <.001), but the effect was estimated as small with an adjust R squared value of .02. Because the statistical effects were small, minimal conclusions were drawn as to the differences between types of leadership experiences or if there were differences between survey years on leadership efficacy for undergraduates at this institution. In addition, because of the small effect size, no conclusion were made to the effect leadership experiences have on predicting leadership efficacy or which type of leadership experience has greater effect on predicting leadership efficacy. It was not concluded that leadership opportunities on college campuses should not be supported because there was statistical significance to support differences and effects, but given the small effect, results were inconclusive. The MSL survey instrument changed between years of data collection, which caused limitations to this study. To the benefit of future studies, the MSL instrument asked questions in the format that now captures more robust data about student participation in leadership experiences during college that can be better explored in future studies. Given the definition of leadership efficacy and magnitude of leadership-related tasks, does the leadership efficacy scale represent the extent to which undergraduates could build leadership capacity through varying levels and types of leadership education offered in college? Future research studies could examine theory of self-efficacy to create a more robust leadership efficacy scale that accounts for differences among populations and varying ways in which students internally see their leadership capabilities. Such research could support the continued call to educators to conduct research on student leadership development and models used in practice to ensure participants reach intended outcomes.
Keywords: higher education; leadership studies; organizational development; leadership efficacy; contemporary leadership; MSL